1989
DOI: 10.1172/jci113900
|View full text |Cite
|
Sign up to set email alerts
|

Expression of class I and class II major histocompatibility antigens on human hepatocellular carcinoma.

Abstract: Previous reports indicate that human hepatocytes do not express class I and class II MHC antigens. Our analyses on 10 human hepatocellular carcinoma (HCC) cell lines by immunofluorescence tests and RIA, demonstrate that all the human HCC cell lines tested express class I MHC antigens and among them, three poorly differentiated human HCC cell lines also express class II MHC antigens. Results of immunoprecipitation and/or Western blotting experiments indicate similarity in the chemical nature of both the class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…Several studies have shown that HLA-DR protein can be expressed by HCC cells; however, its relation to metastatic potential has not been discussed. 21,22 HLA-DR protein is involved in the antigen presenting function of macrophages including dendritic cells. 22 Activated lymphocytes also express the HLA-DR antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HLA-DR protein can be expressed by HCC cells; however, its relation to metastatic potential has not been discussed. 21,22 HLA-DR protein is involved in the antigen presenting function of macrophages including dendritic cells. 22 Activated lymphocytes also express the HLA-DR antigen.…”
Section: Discussionmentioning
confidence: 99%
“…These include hepatitis B virus infection [3][4][5] and hepatoceilular carcinoma {HCC) [2,[5][6][7]. Paterson et al [2] have reported a homogeneous acquisition or enchancement of MHC class I with concomitant expression ofthe invariant chain, /'^2-microglobulin {/32-M).…”
Section: Introductionmentioning
confidence: 99%
“…These may be useful tools for (he study of MHC gene expression and regulation in hepatocytes as well as for the investigation of MHC antigens with transformation of human hepatocytes [5,7,8]. Most antigens, although results have sometimes been at odds [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of MHC expression on human hepatocytes or hepatoma cells were mostly assessed with immunohistochemistry, radioimmunobinding assay or ELISA (Sung et al, 1989;Wadee et al, 1994). Recently, flow cytofluorimetry has been widely used to investigate the antigens expressed on the cell surface of target cells, not only because of its high sensitivity but also of its quantifiability (Anderson et al, 1993;Vidovic et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MHC antigens on human hepatoma cell lines and liver tissues has been reported (Sung et al, 1989;Wadee et al, 1994), and the loss or decrease of MHC class I antigens has been demonstrated in some hepatoma cell lines (Kurokohchi et al, 1996). bated at 37°C in a C02 incubator with 5% C0 2 -Monoclonal antibody (MAb) L243, against the DR region of MHC class II antigens (M090-7360, Becton Dickinson Immunocytometry Systems.…”
mentioning
confidence: 99%